METHANOLIC EXTRACT OF Ficus platyphylla LEAF MODULATES WEIGHT, BLOOD GLUCOSE LEVEL AND SERUM LIPID PROFILES IN WISTAR ALBINO RATS - Ganiyu, Aderounmu Ibrahim; Amuzat, Aliyu Olalekan; Yusuf, Abdurrahman Pharmacy (FUDMA JOURNAL OF SCIENCES, 2023)
Excessive weight gain following the prolonged elevation of blood glucose and lipids is the major driver of obesity, diabetes, and related conditions. This study, therefore, aims to evaluate the effect of Ficus platyphylla leaves extract on body weight, blood glucose levels, and serum lipids of albino rats. Methanolic extract from a sample of the plant’s leaves was first prepared and subjected to phytochemical screening. Doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg were administered to three groups of rats daily while a fourth (control group) received distilled water for 21 days. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, and steroids. A significant (p<0.05) reduction in body weight was observed in the rats administered 100 and 200 mg/kg extract but the reduction is not statistically significant in the 400 mg/kg group. All treatments led to a significant reduction in blood glucose, total cholesterol, triglycerides, and low-density lipoprotein levels with a concomitant rise in high-density lipoprotein cholesterol levels. Our findings demonstrate that the methanolic extract of Ficus platyphylla leaves has an ameliorative effect on body weight, blood glucose, and lipids, and hence the plant could be beneficial to obese and diabetic patients.